Colorimetric determination of ammonia in air using a hanging drop - Felix, E. P.; Cardoso, Arnaldo Alves [UNESP] (Marcel Dekker Inc, 2003)
A simple and sensitive method for determining atmospheric ammonia (NH3), using a hanging drop, is described. A colorimetric sensor is composed of two optical fibers and the source of monochromatic light implemented was a red light emitting diode (LED) (635 nm). Preliminary experiments were carried out in order to optimize the geometry of the sensor. These tests showed that the best signal absorbance was obtained using a 22 muL deionized water drop for sampling the gas and as addition of 4 muL of each of the reactants to form the blue dye (indophenol). Some important analytical parameters were also studied, including sampling time and flow rate. The analytical curve was constructed with a concentration range of 3-20 ppbv of gaseous NH3 standard. The detection limit reached was of ca 0.5 ppbv. It was observed that formaldehyde and diethylamine did not interfere. However, studies showed that hydrogen sulfide caused a negative interference of 20%, when present in the atmosphere in a concentration equal to that of NE3. The method considered here was shown to be easy to apply, making it possible to make a determination every 17 min.
Keywords: ammonia in air; hanging drop; gas generation; optical fibers; air analysis; droplet sensor